Optimization of pre-treatment process of glycerol residue for succinic acid production - Nik Nor Aziati, Abd Aziz (2013)
The purpose of this study is to recover glycerol from the oleo-chemical industry waste through acid pre-treatment process. Pre-treatment intervals parameters (pH, temperature and mass substrate) was obtained from OFAT, while the optimum conditions for the recovery of glycerol obtained by using response surface methodology (RSM). Glycerol concentrations before and after pre-treatment and succinic acid derived from the fermentation process were analyzed using HPLC. FTIR spectrometry was used to identify functional groups of glycerol. The optimum conditions of pH, temperature and substrate mass for glycerol pre-treatment process is at 2.0, 35 ° C and 110.3600 grams respectively. In optimal conditions, the concentration of glycerol after pre-treatment process is 159.3120 g / L. Glycerol is then used in the fermentation by Escherichia coli K-12 types to produce succinic acid of 0.6698 g / L, with initial concentration of glycerol, rotational speed and temperature at 19.6700 g / L, 200 rpm and 37 ° C, respectively. Succinic acid production from glycerol derived from the recovery process is 8.67% lower than the production of succinic acid from commercial glycerol. Therefore, this study was able to demonstrate that the glycerol from the oleo-chemical industry waste can be used in the production of succinic acid.